The Youngest Get the Pill: ADHD Misdiagnosis and the Production of Education in Germany - Amelie Wuppermann; Hannes Schwandt (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Attention Deficit/Hyperactivity Disorder (ADHD) is a leading diagnosed health condition among children in many developed countries but the causes underlying these high levels of ADHD remain highly controversial. Recent research for the U.S., Canada and some European countries shows that children who enter school relatively young have higher ADHD rates than their older peers, suggesting that ADHD may be misdiagnosed in the younger children due to their relative immaturity. Using rich administrative health insurance claims data from Germany we study the effects of relative school entry age on ADHD risk in Europe's largest country and relate the effects for Germany to the international evidence. We further analyze different mechanisms that may drive these effects, focusing on physician supply side and demand side factors stemming from the production of education. We find robust evidence for school-entry age related misdiagnosis of ADHD in Germany. Within Germany and internationally, a higher share of misdiagnoses are related to a higher overall ADHD level, suggesting that misdiagnoses may be a driving factor of high ADHD levels. Furthermore, the effects in Germany seem to be driven by teachers and parents in an attempt to facilitate and improve the production of education.
Keywords: I10; I21; J13; 330